Contract Law and Development - Aristotelis Boukouras (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
We relate the design of contract law to the process of development. In this paper, contract law de fines which private agreements are enforceable (i.e. are binding and enforced by courts) and which are not. Speci cally, we consider an economy where agents face a hold-up problem (moral hazard in teams). The resulting time-inconsistency problem leads to inefficiently low levels of effort and trading among agents. The solution to this problem requires a social contract which meets two conditions: (i) an economywide delegate (judge) responsible for the enforcement of the social contract and (ii) a set of non-enforceable private contracts (regulation). However, because this mechanism is costly, its effectiveness depends on the aggregate production of the economy. To capture the interaction between contract enforcement and development, we introduce a multiperiod economy and show that, in the early stages of development, the mechanism is infeasible. The appearance of enforcement institutions and regulation is delayed for the later stages. At this point of time, the hold-up problem is solved and this spurs economic growth further. Finally, the relationship between economic development and the evolution of contract law may be non-monotonic, which may explain why empirical studies fail to find a robust relationship between the two.
Keywords: D02; D82; D86; K12; O12; O31; O43; 330; contract law; development; enforcement institutions; hold-up; institutional agent; regulation; social contract